Association between changes in adherence to the 24-hour movement guidelines with depression and anxiety symptoms among Chinese adolescents: a prospective population-based study - Herui Wu; Yi-fan Lin; Liwen Yang; Wenjian Lai; Yanzhi Li; Ye Xu; Wanxin Wang; Lei Yang; Ciyong Lu; Bin Yan (Child and Adolescent Psychiatry and Mental Health)
Abstract Background The 24-hour movement guidelines (24-HMG) include screen time (ST), sleep duration, and physical activity. Previous studies have explored the associations of adherence to the 24-HMG with depression and anxiety symptoms among adolescents, ignoring changes in behaviors. This study aimed to examine whether changes in adherence to the 24-HMG were associated with depression and anxiety symptoms among adolescents. Methods We recruited adolescents from Shenzhen, China in 2021 and followed them up 1 year later. Changes in adherence to the individual 24-HMG were categorized into four groups: persistent non-adherence, adherence to non-adherence, non-adherence to adherence, and persistent adherence. Changes in the numbers of adherence to the overall 24-HMG were obtained by subtracting the number of guidelines adhered to in wave 2 from that in wave 1. Results We included 12,570 participants aged 9–18 years with 52.2% boys. Compared with persistent non-adherence for the ST/sleep duration guideline, non-adherence to adherence and persistent adherence were associated with lower depression and anxiety symptoms, but adherence to non-adherence was not. Changes in adherence to the physical activity guideline were not related to outcomes. The β coefficients (95% CIs) for each point increase in changes in the numbers of adherence to guidelines were − 0.58 (− 0.69, − 0.47) and − 0.43 (− 0.53, − 0.33) for depression and anxiety symptoms, respectively. The association of persistently adhering to sleep guideline with anxiety symptoms and the associations of changes in the numbers of adherence to the 24-HMG had sex differences. Conclusions Maintaining and strengthening healthy movement behaviors to meet more guidelines of the 24-HMG, especially sleep and ST, may be beneficial for preventing depression and anxiety symptoms in adolescents.